Factors influencing issuers’ sukuk structure preference: the case study of KSA Banks - N. Hussain, Hanadi Abu Baker; Adewale, Abideen Adeyemi; Engku Ali, Engku Rabiah Adawiah (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM)., 2018)
The purpose of this research paper is to examine the factors that influence the issuers’ sukuk structures and the impact of sukuk on the performance of the Kingdom of Saudi Arabia (KSA) sukuk issuing listed banks using the pooled OLS regression and the random effects panel models. The findings of this study show that while both bank size and the issued amount of sukuk positively affect the performance of the sukuk issuing listed banks of the KSA, a negative effect of the leverage ratio on performance was noted. Meanwhile, the sukuk dummy is reported to be statistically insignificant though it has a positive and negative magnitude in both models. Nevertheless, given the insignificance of the dummy variable, we can conclude that the factors that affect the issuers’ sukuk structure in the case of the sukuk issuing listed banks of the KSA is profit maximization rather than Shari’ah compliance. Thus, this study may offer some policy insights for policymakers in KSA especially because sukuk issuance boost banks performance.